Organizations and People for Sustainability - ROMANELLI, Mauro (Management Dynamics in the Knowledge Economy, 2018)
Organizations proceed towards sustainability rediscovering the role of ethics and human resources. Managing human resources systems and designing work relationships is leading organizations to follow ethical approaches, values, and culture in starting entrepreneurial ventures and doing business for building sustainable development. Organizations should sustain and encourage ethical behaviors at work creating organizational environments ethics-oriented by managing, valuing people and developing the human resources capabilities. Designing a path to drive organizations towards sustainability relies on defining the relationships of employment ranging from the psychological contract to designing contractual architectures, governing and managing human resources and promoting ethics by sustaining an organizational culture ethics-oriented.